ANALYSIS OF THE DYNAMICS OF MANIFESTATION OF OCCUPATIONAL BURNING SYNDROME IN MEDICAL WORKERS IN CONDITIONS OF COVID-19 (Psychology Travelogs, 2021)
The article presents and analyzes the results of two studies, in the process of which a total of 134 active health workers were examined, whose professional activity in medical institutions for a long time takes place in quarantine measures in connection with the COVID-19 pandemic. With the help of V. Boyko's method, the level of emotional burnout and its structure in medical workers in 2020 was diagnosed. in the initial stage of quarantine related to the COVID-19 pandemic and in the process of long-term professional activity in the conditions of the pandemic (2021). An analysis of the dynamics of occupational burnout in the departments of direct and indirect counteraction to COVID-19 was also performed. Analysis of the results of our study allows us to conclude that the risk of burnout among health care workers who directly oppose COVID-19 due to the high level of CMEA development is extremely high - 3-8 times higher than among health care workers working in conditions which does not provide direct counteraction to COVID-19. These indicators are confirmed by levels of statistical reliability of research results not only p≤0.05, but also levels p≤0.01. This picture determines the need for special psychological measures and attentional-oriented psychological work among this contingent of health workers.
Keywords: emotional burnout syndrome, occupational burnout, pandemic COVID-19, professional activity in conditions of stress, activity of medical workers in conditions of pandemic COVID-19